A System Dynamic Model for Shallow Urban Lake Coupling With the Interference of Chlorine - Yan, Zhiqiang; Fan, Chen; Xia, Beicheng (Journal of Environmental Accounting and Management, 2026)
Ecological models play an important role in lake eutrophication research and management. Many integrated system models have been developed since the 1970s. However, their fixed structure limits flexibility and applicability in urban landscape lakes. An ecosystem dynamic model was constructed to simulate ecological restoration of an urban shallow lake under the interference of chlorine. The model was validated using the monitoring data of an urban lake in Guangzhou. The correlation coefficient (R), root mean squareerror-observations standard deviation ratio (RSR) and index of agreement (IOA) were calculated to evaluate accuracy and reliability of the model and their values for all of the compared variables were significant, less than 0.7, and larger than 0.6, respectively, which reflected good agreement of the model. The results give important insight into understanding eutrophic dynamic process in urban shallow lake. Furthermore, the exhibit model has great applicability in management of urban shallow lakes.